2004
DOI: 10.1517/14712598.4.2.145
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of cellular transplants by magnetic resonance imaging and positron emission tomography

Abstract: Cellular loss is a common pathological observation in many disease conditions. Recent evidence that these cells can be replaced has generated huge excitement over possible clinical applications. The use of stem or progenitor cells, which can differentiate into site-appropriate phenotypes required to "repair" the damaged tissue, has already demonstrated potential in animal models, but many aspects of this novel treatment strategy require further elucidation. Most importantly, the monitoring of the safety of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Clinical application of neonatal stem cell treatment will require noninvasive tracking of cells to (1) demonstrate accuracy of implantation; (2) monitor cell migration, proliferation, and location; and (3) assess structural tissue recovery or, conversely, adverse host reactions. Several reports have demonstrated that iron‐labeled NSCs can be tracked using magnetic resonance imaging (MRI)13–15 but did not use MR evaluation for long periods of time (>6 months) and did not correlate NSC behavior with the dynamics of underlying pathology—critical for the actual translation of NSC‐based therapeutics to patients 7, 11, 16, 17. The ability to monitor NSCs for extended periods is particularly important in newborns because long‐term implantation may pose unanticipated risks to the developing brain.…”
mentioning
confidence: 99%
“…Clinical application of neonatal stem cell treatment will require noninvasive tracking of cells to (1) demonstrate accuracy of implantation; (2) monitor cell migration, proliferation, and location; and (3) assess structural tissue recovery or, conversely, adverse host reactions. Several reports have demonstrated that iron‐labeled NSCs can be tracked using magnetic resonance imaging (MRI)13–15 but did not use MR evaluation for long periods of time (>6 months) and did not correlate NSC behavior with the dynamics of underlying pathology—critical for the actual translation of NSC‐based therapeutics to patients 7, 11, 16, 17. The ability to monitor NSCs for extended periods is particularly important in newborns because long‐term implantation may pose unanticipated risks to the developing brain.…”
mentioning
confidence: 99%
“…This is caused by mounting evidence that brain tumors may be caused by a single NSC that did not differentiate (22). The ability to monitor cell therapy in vivo is therefore desirable because it may provide more control over the activity of NSCs (23). One possibility is that stem cells will be engineered with a suicide gene (24) that could be activated if transplanted cells did not behave in a therapeutic manner.…”
Section: Stem Cell Transplantation In Brain Tumors: a New Field For Mmentioning
confidence: 99%
“…Paradoxically, the inflammatory and immune response to transplanted cells is also known to lead to behavioral improvements [4] indicating that the relationship between functional repair and graft survival is not as straightforward as it is often assumed. It also remains largely unknown how additional Limiting these anatomical analyses to post-mortem excised tissue, nonetheless, confines this approach to a snapshot view of the histological landscape and therefore complicates assertions as to how changes occurred or how these relate to behavioral improvements [9].…”
Section: How Do Neural Stem Cells Promote Behavioral Recovery?mentioning
confidence: 99%
“…The ability to visualize detailed anatomy repeatedly and non-invasively in vivo offers the opportunity to investigate how stem cell transplantation affects the damaged brain [9]. Both magnetic resonance imaging (MRI) and positron emission tomography (PET) are excellent in vivo imaging techniques to probe cell therapy in both preclinical models and clinical applications ( Table 1).…”
Section: The Necessity Of In Vivo Imaging To Elucidate Stem Cell-medimentioning
confidence: 99%